Policy Considerations to Promote Equitable Cervical Cancer Screening and Treatment in Peru - Andrea Thoumi; Sarah J. Bond; Mary Elizabeth Dotson; Marlee Krieger; Patricia J. Garcia; Nirmala Ramanujam (Ubiquity Press, 2021)
Background: Cervical cancer is one of the leading causes of death among Peruvian women. Women seeking screening or treatment services experience delays in receiving screening results provided at community clinics or district hospitals, and lack sufficient resources to pay out-of-pocket to travel to the capital city of Lima for specialized treatment. Continued disparities in health outcomes and systemic barriers to accessing services suggest there are gaps between policy measures and implementation. Objectives: We aim to understand why national policies and clinical pathways that are aligned to global standards have been insufficient in improving cervical cancer screening and treatment in Peru, particularly among women who experience systemic exclusion from health services. Methods: We conducted a policy analysis based on a literature review (2005-2020), in Spanish and English, on PubMed, Global Health, Scopus, EconLit, Lilacs, and Scielo using a value-based care framework. Findings: The main barriers included unequal distribution of health infrastructure and health care workforce, and differences in access to health insurance. Additional barriers, including limited political will and support, limit efforts to prioritize the implementation of cervical cancer policies. We propose policy considerations in redesigning payment models, expanding healthcare workforce, generating costing and policy evidence, and reviewing policies for point-of-care technologies. Conclusions and Recommendations: The barriers identified in this literature review are applicable not only to cervical cancer care, but to primary health care in Peru. Systematic policy changes that address root causes of health inequities and are implemented at scale are needed to advance health reform efforts.